2007
DOI: 10.1007/s10803-006-0331-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Toddlers with Autism Spectrum Disorders

Abstract: Although autism spectrum disorders (ASD) prevalence is higher in males than females, few studies address sex differences in developmental functioning or clinical manifestations. Participants in this study of sex differences in developmental profiles and clinical symptoms were 22 girls and 68 boys with ASD (mean age = 28 months). All children achieved strongest performance in visual reception and fine motor followed by gross motor and language functioning. Sex differences emerged in developmental profiles. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
181
5
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(206 citation statements)
references
References 33 publications
17
181
5
3
Order By: Relevance
“…Exploratory analyses of gender differences in the autistic sample yielded significantly higher performance on both direct and indirect tasks of male ASD participants compared to females. Recently, a growing number of studies have reported gender differences within ASD on various behavioral measures including cognitive abilities (Boelte et al 2011;Lai et al 2011;Lord et al 1982) and social cognition in particular (Carter et al 2007;Golan et al , 2007Sucksmith et al 2013). In contrast to our results, previous studies have found higher facial emotion recognition performance in adult females with ASD compared to males Sucksmith et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Exploratory analyses of gender differences in the autistic sample yielded significantly higher performance on both direct and indirect tasks of male ASD participants compared to females. Recently, a growing number of studies have reported gender differences within ASD on various behavioral measures including cognitive abilities (Boelte et al 2011;Lai et al 2011;Lord et al 1982) and social cognition in particular (Carter et al 2007;Golan et al , 2007Sucksmith et al 2013). In contrast to our results, previous studies have found higher facial emotion recognition performance in adult females with ASD compared to males Sucksmith et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, previous studies have found higher facial emotion recognition performance in adult females with ASD compared to males Sucksmith et al 2013). However, in line with our results, Carter et al (2007) found that parents reported higher social competences for boys with ASD than for girls and Golan et al (2007) report higher performance on a naturalistic emotional prosody task in autistic males compared to females. Thus, in more complex naturalistic settings, such as inferring mental states from speech and videos, or interacting in real life situations, autistic males seem to have an advantage over females.…”
Section: Discussionsupporting
confidence: 64%
“…Participants for the present study were drawn from two ongoing longitudinal studies of families of children with ASD, one focused on families with toddlers (Carter et al, 2007) and one focused on families with adolescents and adults (Seltzer et al, 2003; Shattuck et al, in press). Families of toddlers were recruited through early intervention providers, autism specialty service providers, physicians, and local conferences and events for families of children with ASD.…”
Section: Methods Participantsmentioning
confidence: 99%
“…However, in contrast to the increased risk of suicide in males in the general population, a recent study reported a loss of this typical sex difference, leading to a higher relative risk in females with ASD compared to those without ASD (Hirvikoski et al 2016). Over the last few years, an increased awareness of sex differences in brain and behaviour studies in ASD is an encouraging trend (Alice et al 2007;Baron-Cohen et al 2011;Lai et al 2013;Mandy et al 2011) that should be extended into the matrix of ASD and suicidality.…”
Section: Developmental-contextual Factors: Sex and Agementioning
confidence: 99%